PROVISION OF THE DEVELOPMENT OF THE PROFESSIONAL COMPETENCE OF TEACHERS IN INCLUSIVE EDUCATION - Prudnikova, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Many educational researchers explain and appreciate the special importance of improving the professional competence of teachers in this era of change in Latvia when the Ministry of Education and Science has envisaged one of the most comprehensive reforms by implementing competency based education. Inclusive education implies that teachers have to master appropriate general skills which will help them to grasp topicalities, to be the leaders of changes and to adequately innovate the learning process where all different needs of learners are met by increasing participation opportunities of each and everybody in learning, culture and different communities and by reducing exclusion within and from educational process. The aim of the study was to clarify the point of view of teachers about the quality of content of the provided professional development. The set of questionnaires was developed by teachers of general education institution where learners with special needs were included. The survey studied the motivation of teachers to participate in professional development courses/seminars/projects; the opinion of respondents about the organization, form and content of continuing professional development in line with their needs. Conclusions: The development of professional competence of teachers in Latvia on national level is implemented according to the pedagogical needs modelling method which supports autonomy and which is self-guided by free self-education initiative of teachers. The survey is based on the fact that teachers lack knowledge and skills to appropriately assess and formulate their continuous professional development needs.